Situation of Anticoagulant Prescription on Outpatients in Ha Dong General Hospital - Minh Hung, Pham; Truong Giang, Nguyen; Bao Tuan, Dang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
Objective: The study aims to describe the current situation of prescribing oral anticoagulants for outpatients in Ha Dong General Hospital. Subjects and research methods: A retrospective descriptive study on the prescription of oral anticoagulants for all outpatients in Ha Dong General Hospital from January 2023 to April 2024. Results: Three oral anticoagulants were prescribed: acenocoumarol, dabigatran, and rivaroxaban. Among 121 patients included in the study, 91.7% were prescribed anticoagulants for atrial fibrillation and artificial heart valves. The number of prescriptions for acenocoumarol was the highest (81.4%) among the total prescriptions for the three drugs. The rate of appropriate dosing for direct oral anticoagulants (DOACs) was 59.9%. The percentage of patients achieving a time in therapeutic range (TTR) >65% using acenocoumarol was 18.6%. Conclusion: 100% of patients were prescribed anticoagulants in accordance with the therapeutic guidelines. However, the rate of appropriate oral anticoagulant dosing for outpatients remained low (59.9%). The proportion of patients with good INR control, defined as the percentage of time the INR remained within the desired therapeutic range above 65%, was still low, with only 18.6% achieving a TTR >65%. There is a need to strengthen the knowledge and prescribing practices of anticoagulants among doctors in hospitals to gradually ensure the rational use of anticoagulants.